KALAM MODERN: SEBUAH PARADIGMA BARU - Febri Hijroh Mukhlis (Jurnal Ilmiah Ilmu Ushuluddin, 2018)
This study highlights the tendency of ʿIlm al-Kalām or sometimes called "Islamic scholastic theology" which is one of the less developed Islamic studies. The author proposes that developing this study requires criticism and a new, more contextual approach. One of the most urgent in Kalam's study is to include contemporary contextual themes such as social, humanity, culture and technology. Therefore, the study orientation of Kalam on the issue of divinity (theocentric) must be transformed into the issue of humanity (anthropocentric). For this reason, Kalam's study must be interdisciplinary with the social sciences and other modern humanities.